Pengaturan Hukum Pidana Pelaku Penggelapan Jual Beli Online - I Gusti Ngurah Agung Bagus Bima Putra; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi (Jurnal Analogi Hukum, 2021)
Today in the world of electronic transactions many are found deviant actions, and not based on existing legal norms, most of which occur in online buying and selling systems. Buying and selling is online buying and selling sometimes based only on trust which means the buying and selling actor is sometimes unclear, therefore many prefer COD or Cash On Delivery and or payment at the place of delivery of goods. Be careful in making payments via transfer, first research the reputation of the seller who offers goods in accordance with the posted, check the existence of the seller's offline store or the seller's business license. There is also a problem formulation (1) How is the legal arrangement regarding the actions that have been done by business actors against consumers on online buying and selling sites? (2) What criminal sanctions are imposed on perpetrators of embezzlement crimes on online buying and selling sites? This research uses normative methods because there are still vague norms, based on the opinion of legal experts. If a person has fulfilled all the elements of the crime of embezzlement, then he can be called a perpetrator.